2010
DOI: 10.1002/ibd.21134
|View full text |Cite
|
Sign up to set email alerts
|

CD24 is upregulated in inflammatory bowel disease and stimulates cell motility and colony formation

Abstract: This is the first study to report upregulation of CD24 in regenerating tissue in IBD. This may be regulated by Wnt signaling and can confer enhanced colony forming ability and enhanced cell motility-features that may be important in tissue healing in the colon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 32 publications
(29 reference statements)
4
32
0
Order By: Relevance
“…We found that the motility of CD24 + cells was higher than that of CD24 -cells. This finding is consistent with a previous study in which forced expression of CD24 in HCT116 human colon cancer cells significantly increased cell migration in wound-healing assays (22). We also performed a wound-healing assay in naïve RMCCA1 cells and found that RMCCA1 cells at the wound edge expressed higher levels of CD24, suggesting that CD24 -cells can give rise to CD24 + cells that have a greater ability to migrate.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that the motility of CD24 + cells was higher than that of CD24 -cells. This finding is consistent with a previous study in which forced expression of CD24 in HCT116 human colon cancer cells significantly increased cell migration in wound-healing assays (22). We also performed a wound-healing assay in naïve RMCCA1 cells and found that RMCCA1 cells at the wound edge expressed higher levels of CD24, suggesting that CD24 -cells can give rise to CD24 + cells that have a greater ability to migrate.…”
Section: Discussionsupporting
confidence: 92%
“…We demonstrated for the first time that MMP-7 was highly expressed in CD24 + cholangiocarcinoma cells. Previous studies have demonstrated that MMP-7 plays a key role in the mechanism of cancer invasion via proteolytic cleavage of the extracellular matrix tissues (22). MMP-7 has also been shown to activate other MMPs, such as pro-MMP-2 and pro-MMP-9, and to inhibit E-cadherin function by inducing ectodomain shedding of E-cadherin (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…The antibodies used in this study were validated by Western blotting as described previously [15]. For validation of anti-CD44 antibody (CD44 (156-3C11), cell signalling, #3570) specificity, Western blotting was performed on whole cell lysates of MCF-7 and MDA-MB231 human breast cancer cell lines (obtained from the American Type Culture Collection; Rockville, MD, USA).…”
Section: Validation Of Antibodies' Specificitymentioning
confidence: 99%
“…Likewise, a lack of correlation between CD34 marker and clinical and pathological factors including; lymphatic invasion, gender, age and stage of differentiation were also confirmed in the study by Wang et al (2004). In the study of Ahmed et al (2010), as well as, Nosrati et al (2014) on colorectal cancer, no association was reported between the CD34 expression and clinicopathologic factors. In contrast, increasing the CD34 marker expression was positively correlated with tumor stage, infiltration and lymph node and therefore, it was concluded that this marker in GC is correlated within the disease development (Chen et al, 2008).…”
Section: Discussionmentioning
confidence: 58%